Pengaruh Persaingan terhadap Penjualan di Warung Koki Kaki Lima Cakung - Nahason Sitohang; Maria Fransiska Laim Onggur (Master Manajemen, 2024)
The purpose of this research is to find out how much influence competition has on sales at warung koki street street. The formulation of the problem in this research includes whether price, place, promotion, distribution, people, process and product influence sales at warung koki kaki lima cakung. This research is field research with descriptive quantitative research methods. Primary and secondary data sources. Data collection techniques use observation, questionnaire and documentation methods. The sample in this research was 99 consumers of warung koki street street, who then analyzed the data using validity tests, reliability tests, normality tests and simple linear regression. The competition variable (x) has a significant influence on sales at the cakung street food stall, east jakarta. It can be seen that tcount is = 2.670> ttable is = 2.024, so it can be concluded that ha is rejected and ha is accepted. Based on the research results by comparing the fcount>ftable values, it was obtained that it was 7.131 > 4.10, which means positive. Meanwhile, a p-value of 98 was obtained in the sig column, 0.011 < 0.05, meaning it is significant. So it can be concluded that competition can have a significant positive effect on sales at warung koki kaki cakung.